HUBUNGAN TINGKAT PENGETAHUAN DENGAN KESIAPAN IBU DALAM MENGHADAPI MENOPAUSE DI DESA BERANGAS TIMUR KAB. BARITO KUALA - Kusumawati, Sixtia (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2019)
Women approaching menopause to decrease the various functions of the body, so that will have an impact on discomfort in living life. Needed to be balanced by a positive attitude or knowledge sufficient information, so that the mother is more prepared to deal with menopause either prepared physically, mentally, and spiritually. Preparedness in the face of maternal menopause are based on knowledge will be more mature than the mother's readiness in dealing with menopause that are not based on knowledge. The purpose of this study to determine the relationship with the level of knowledge mother readiness in facing menopause in Berangas Timur village. This research uses a descriptive analytic crosssectional design. Sampling using purposive sampling technique as many as 100 people. Data analysis using Spaerman 's rank correlation test with a 95 % confidence level and significance level < 0.05. It can be concluded that most of the knowledge about menopause in a category quite as many as 53 people (53 %) and preparedness to face menopause mostly are prepared as much as 60 0rang (60 %), with the end result there is a significant relationship between knowledge about menopause with readiness mother in the face menopause Kingdom Banjarmasin Kuin the Health Clinic with a value of Ï = 0.003 at the significance level 0.05. Keywords: Knowledge, preparedness in the face of Menopause